An Overview of Reusability of Software Components (International Journal of Engineering and Computer Science, 2017)
Reuse of software is required to improve the quality and productivity. If their need some changes in the existing software than software can be reused rather than creating software from scratch. Software reuse is the process of creating software systems from existing software rather than building them from scratch. This paper gives details about various concepts of reuse. For making some changes in software no need to change the whole software working particular changes can be done with reuse in existing software. This paper explains about the things in software that can be reused, various techniques of reuse and advantages and drawbacks of reuse. A component reuse is famous for reuse. The quality of software depends on the quality of the reusable component.